2007
DOI: 10.1002/cne.21490
|View full text |Cite
|
Sign up to set email alerts
|

Detection and localization of an estrogen receptor beta splice variant protein (ERβ2) in the adult female rat forebrain and midbrain regions

Abstract: Estrogens regulate neural processes such as neuronal development, reproductive behavior, and hormone secretion, and signal through estrogen receptor (ER) alpha and ERbeta (here called ERbeta1). Recent studies have found variations in ERalpha and ERbeta1 mRNA splicing in rodents and humans. Functional reporter gene assays suggest that these splicing variations alter ER-mediated transcriptional regulation. Estrogen receptor beta 2 (ERbeta2), an ERbeta1 splice variant containing an 18 amino acid (AA) insert in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 63 publications
3
51
0
Order By: Relevance
“…These are brain areas that are highly sensitive to circulating E2. If Handa et al 22 are correct, our result that ERb ins mRNA decreases just after birth, suggests that this splice variant of ERb may be playing some modulatory role during embryonic life. One such function could be protection of the fetus from circulating high-level E2 by being a dominant repressor of both ERa and ERb1.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…These are brain areas that are highly sensitive to circulating E2. If Handa et al 22 are correct, our result that ERb ins mRNA decreases just after birth, suggests that this splice variant of ERb may be playing some modulatory role during embryonic life. One such function could be protection of the fetus from circulating high-level E2 by being a dominant repressor of both ERa and ERb1.…”
Section: Discussionmentioning
confidence: 56%
“…Handa et al 22 have hypothesized that ERb ins may act as a dominant negative, low-affinity ER in the brain. Their hypothesis is based on their IHC observation of colocalization of ERb1 and ERb ins in the preoptic area, the bed nucleus of stria terminalis, and the Dynamics of estrogen receptors in the brain N Sugiyama et al amygdala of the adult rat brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also increasing evidence that a subpopulation of ERs are found at extranuclear sites and specifically at synapses, a subcellular localization consistent with the ability of these receptors to couple to second messenger signaling pathways. Others have suggested that rapid actions of estrogens are mediated by splice variants of ERs (Toran-Allerand, 2004;Zhao et al, 2005;Chung et al, 2007;Ishunina and Swaab, 2008;Ishii et al, 2011;Kobayashi et al, 2011;Wu et al, 2012).…”
Section: Coupling Of Estrogen Receptors To Second Messenger Systemsmentioning
confidence: 99%
“…Another potential mechanism that has been proposed is the identification of splice variants of both ERa and ERb in neuronal tissue with extranuclear expression (Price et al, 2001;Ishii et al, 2011). Splice variants for both receptors can generate receptors lacking specific motifs, such as the nuclear localizing signal, or even the N or C termini (Price et al, 2001;Chung et al, 2007;Ishunina and Swaab, 2008;Ishii et al, 2011;Kobayashi et al, 2011). Therefore, it is plausible to suggest that these splice variants could function solely as a membrane ER, capable of coupling to second messenger signaling pathways.…”
Section: B Surface Expression Of Ersmentioning
confidence: 99%